Robust interpolation of agricultural census data to hydrological units and implications for diffuse pollution modelling - Paulette E. Posen; Michael G. Hutchins; Andrew A. Lovett; Helen N. Davies (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
Diffuse pollution from agriculture is often responsible for observed concentrations of agricultural compounds being in excess of the upper limits prescribed by the EU Water Framework Directive (WFD) in some river catchments and reductions in these concentrations will require widespread changes in farm practice. One of the aims of the UK RELU Catchment Hydrology, Resources, Economics and Management (ChREAM) study is to assess likely impacts of WFD implementation on agricultural land use and consequent implications for water quality and farm incomes. An element of this work involves updating an existing diffuse pollution model to reflect present-day land use profiles. Combining agricultural land use data with hydrological spatial units can involve a number of problems arising from the integration of a variety of data formats at a range of spatial and temporal resolutions and the aggregation of source data over different spatial extents. This paper assesses uncertainty arising from areal interpolation of agricultural census data to hydrological units. The work is illustrated through a case study of the River Derwent catchment in north-east England. The study identifies the range of spatial resolutions at which robust estimations of agricultural land use can be made and examines the implications for diffuse pollution modelling.
Keywords: 330; agricultural census; land use; diffuse pollution modelling; Water Framework Directive; Landwirtschaftliche Bodennutzung; Düngemittel; Gewässerbelastung; Umweltpolitik; Großbritannien